Efektivitas Metode Index Card Match dalam Meningkatkan Penguasaan Kosakata Bahasa Arab Siswa Kelas IV Sekolah Qur’an Ibnu Katsir - Hidayat, Fajar; Sya'bani, Muhammad Zaky; Kasmudi (Program Studi Pendidikan Bahasa Arab, 2024)
The aim of this research is to determine the level of success and effectiveness of using the Index Card Match learning method in mastering Arabic vocabulary for class IV students at the Ibnu Katsir Qur'an School in Bandar Lampung. The questions in this research include